1986
DOI: 10.1037/0012-1649.22.3.291
|View full text |Cite
|
Sign up to set email alerts
|

Marital quality and mother–child and father–child interactions with school-aged children.

Abstract: The objective of the present study was to examine parent-child interactions with school-aged children in the context of the parents' marital relationship. Sixty families with a school-aged child served as subjects. Mother-child and father-child teaching interactions were videotaped, from which frequency counts of efficacious teaching behaviors were obtained for each parent-child teaching interaction. Parents completed a self-report measure of marital problems. A dyad score of marital problems was formed by add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
92
0
3

Year Published

1988
1988
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(102 citation statements)
references
References 22 publications
7
92
0
3
Order By: Relevance
“…This finding was significant for both mothers and fathers, even after controlling for demographic characteristics and the overall quality of parent-child interactions during infancy. These findings are congruent with previous work with older preschool and school-aged children, which found that supportive and satisfying marital relationships during childhood were predictive of stimulating parent language input (Brody et al, 1986;Pratt et al, 1992). The findings of this study extend the existing knowledge to families with younger children, demonstrating that the quality of the marital relationship during infancy may be related to the language used by mothers and fathers during toddler years, a critical time for language development.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…This finding was significant for both mothers and fathers, even after controlling for demographic characteristics and the overall quality of parent-child interactions during infancy. These findings are congruent with previous work with older preschool and school-aged children, which found that supportive and satisfying marital relationships during childhood were predictive of stimulating parent language input (Brody et al, 1986;Pratt et al, 1992). The findings of this study extend the existing knowledge to families with younger children, demonstrating that the quality of the marital relationship during infancy may be related to the language used by mothers and fathers during toddler years, a critical time for language development.…”
Section: Discussionsupporting
confidence: 83%
“…Existing research suggests that the quality of early family relationships, including the motherfather-child relationship as well as the mother-father relationship may impact the way parents interact with their children Brody et al, 1986;Cox et al, 1989;Grych, 2002;Lindahl et al, 1997;Pratt et al, 1992;, however, it is necessary to extend this research to specifically consider the vocabulary used by parents in interactions with their younger language-learning children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Impressive correlations between prebirth marital quality and parenting behavior with infants have been documented in several samples (Cox, Owen, Lewis, & Henderson, 1989;Grossman, Eichler, & Winikoff, 1980;Heinicke et al, 1986;Lewis, Tresch-Owen, & Cox, 1988). More harmonious marriages have been linked with developmental progress in infants and toddlers (Dickie, 1987;Easterbrooks & Emde, 1988;Goldberg & Easterbrooks, 1984) and young school-age children (Brody, Pillegrini, & Sigel, 1986;R A. Cowan, Cowan, Schulz, & Heming, in press).…”
Section: Role Of the Marriagementioning
confidence: 99%